Pengaruh Bauran Pemasaran terhadap Minat Beli pada Iphone 15 Pro Max di Kota Palembang - Yumi Lestari; Yulia Hamdaini Putri; Aslamia Rosa (STIKes Ibnu Sina Ajibarang, 2025)
The research was conducted to examine the influence of the marketing mix (product, price, place, and promotion) on consumers' purchase intention of the iPhone 15 Pro Max in Palembang City. The research employed a quantitative approach with purposive sampling involving 200 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that all four elements of the marketing mix have a significant effect on purchase intention, both simultaneously and partially. Product and promotion emerged as the dominant factors influencing consumer decisions. This study provides important implications for Apple’s marketing strategies and for local business actors in the premium technology industry.